Downregulation of receptor tyrosine kinase-like orphan receptor 1 in preeclampsia placenta inhibits human trophoblast cell proliferation, migration, and invasion by PI3K/AKT/mTOR pathway accommodation. (July 2019) - Chen, Jie; Yue, Chongyu; Xu, Jine; Zhan, Ying; Zhao, Han; Li, Yan; Ye, Yuanhua
Abstract: Introduction: Invasive deficiency of the trophoblast and poor remodeling of the uterine spiral arteries were probably the primary pathogenesis causes of preeclampsia (PE). The expression of receptor tyrosine kinase-like orphan receptor 1 (ROR1) during embryogenesis had been previously confirmed and was closely related to the function of tumor cells, which was similar to the characteristics of trophoblasts. In this work, we investigated the expression profile of ROR1 in preeclampsia placentas and the functional role of ROR1 in trophoblast cells, as well as the associated molecular mechanisms. Methods: The localization expression of ROR1 in the placenta was detected by immunohistochemistry in 20 cases of normal term pregnancy, preterm delivery, late-onset severe PE, and early-onset severe PE, respectively. The expression levels were determined by fluorescence quantitative PCR and Western blot. The influence of ROR1 on trophoblast proliferation, migration, invasion, and potential regulatory pathways was evaluated in HTR-8/SVneo cell lines by transient transfection methods. Results: The levels of ROR1 in the placental tissues in PE were significantly lower than those in normal term pregnancy and preterm delivery. Moreover, the expression levels of ROR1 in early-onset severe PE were significantly lower than those in its late counterparts. ROR1 overexpression increased cell proliferation, migration, and invasion of HTR-8/SVneo cells, whereas its silencing had the opposite effect. Meanwhile, the phosphorylation levels of critical kinases in the PI3K/AKT/mTOR pathways were increased by ROR1 overexpression, whereas they were decreased by the silencing of ROR1. Conclusion: ROR1 might be involved in the development of PE through regulating trophoblast viability, migration, and invasion by PI3K/AKT/mTOR signaling pathway. Highlights: ROR1 protein is abnormally down-regulated in the placenta of preclampsia ROR1 protein regulated the proliferation, migration and invasion of trophoblast cells. ROR1 may function by regulating PI3K/AKT/mTOR pathway.